Helicobacter pylori Infection in Geriatric Patients: Current Situation and Treatment Regimens - Huang, Qiuyue; Jia, Xiaofen; Chu, Yingming; Zhang, Xuezhi; Ye, Hui (Frontiers in Medicine, 2021)
Helicobacter pylori (H. pylori) has so far infected more than half the global population. It is the most important and controllable risk factor for gastric cancer. The elderly, who are at a higher incidence of the infection, are also commonly found to develop antibiotic resistance. The symptoms, diagnosis, clinical features (of gastric or extra-digestive diseases), and treatment of H. pylori infection in the elderly, are different from that in the non-elderly. Health conditions, including comorbidities and combined medication have limited the use of regular therapies in elderly patients. However, they can still benefit from eradication therapy, thus preventing gastric mucosal lesions and gastric cancer. In addition, new approaches, such as dual therapy and complementary therapy, have the potential to treat older patients with H. pylori infection.